Integration of PV Distributed Generator in Electrical Distribution System with Electric Vehicles Charging Stations Considering Uncertainties using Chaotic SSA Algorithm - Mohamed Zellagui (Revue des Énergies Renouvelables, 2021)
The penetration of renewable energy resource units in the Electrical Distribution System (EDS) has gradually increased. In addition to that, the interest in the electrification of the transport sector has brought about increasingly significant incentives for the integration of Electric Vehicles Charging Station (EVCS). In this regard, the planning of the installation of PV source-based Distributed Generation (DG) units in EDS considering EVCS should be carefully considered to avoid stressing the EDS. This paper applied various Chaotic Salp Swarm Algorithm (CSSA) based various chaotic maps methods with the multi-objective functions that are considered minimizing simultaneous the Active Power Loss (APL), the Annual Losses Cost (ALC), and the Total Voltage Deviation (TVV) in EDS. The proposed algorithms are tested on a standard IEEE 69-bus system that is used to demonstrate the feasibility of the CSSA algorithm in allocating the DG units by considering the uncertainty of the power delivered by the DG as well as the variation of load demand and EVCS in 24 hours. Furthermore, the overall EDS performances are also enhanced with simultaneous placement of both devices.